Meningkatkan Kesejahteraan Subjektif Pasien Gagal Ginjal Kronis Melalui Terapi Kognitif Perilaku Religius - Elda Trialisa Putri; Qurotul Uyun; Rr Indahria Sulistyarini (JIP (Jurnal Intervensi Psikologi), 2016)
The purpose of this study is to examine the effectiveness of religious cognitive behavioral therapy in improving subjective well-being of chronic kidney disease patients. The hypothesis of the study was that there is a significant difference in the subjective well-being between experimental and control groups. Four chronic kidney disease patients with age between 22-45 years old, Muslim, and suffering chronic kidney disease more than 6 months participated this study. The design of this experiment was a quasi experiment with pretest-posttest control group design and follow up. Data were collected with satisfaction with Life Scale (SWLS) from Diener, Emmons, Larsen and Griffin's Scale (1985) and Positive Affect and Negative Affect Schedule (PANAS) from Watson, Clark, and Tellegen's scale (1988). Independent sample t-test was conducted to analyze the data. The result showed that there was a difference life satisfaction between the experimental and control group (t=4, 287, p = 0, 005 (p<0,0l). Also, there were difference on an affection score between the experimental and control group (t = 4, 407, p = 0, 005 (p<0,0l). Keywords: religious cognitive behavioral therapy, subjective well-being, life satisfaction, affection, chronic kidney disease